(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Laser Powder-Directed Energy Deposition (LP-DED) has excelled as a technology that can produce parts with large dimensions in less time. Furthermore, the micro-milling process can be combined to provide a uniform surface and a high quality of roughness that directly impacts osteointegration and cellular adhesion. This paper aimed to manufacture bulks produced by LP-DED with two different powders and different laser powers. In sequence, the milling process was used to create six channels and evaluate the influence of the feed per tooth (fz) on the bulk surface. The values obtained from the as-built bulks revealed the impact of the laser power and powder features on the surface of the bulks, obtaining values around 30-55 ?m for the Sq and 20-45 ?m for the Sa, respectively. These values were reduced when applying micro-milling from 1.0 to 1.5 ?m in terms of Sa and 1.5 to 2.5 ?m for the Sq. Regarding Skewness and Kurtosis, the results revealed Ssk > 0, indicating a surface with greater valley concentration, and in most cases, Sku > 3, describing the prevalence of sharp peaks or valleys. This surface microtopography can provide cell housing and form a bone matrix around the implant.